Human resources for refraction services in Central Nepal. (5th May 2015) - Kandel, Himal; Murthy, GVS; Bascaran, Covadonga
<x xml:space="preserve">Abstract</x> Background Uncorrected refractive error is a public health problem globally and in Nepal. Planning of refraction services is hampered by a paucity of data. This study was conducted to determine availability and distribution of human resources for refraction, their efficiency, the type and extent of their training; the current service provision of refraction services and the unmet need in human resources for refraction in Central Nepal. Methods This was a descriptive cross‐sectional study. All refraction facilities in the Central Region were identified through an Internet search and interviews of key informants from the professional bodies and parent organisations of primary eye centres. A stratified simple random sampling technique was used to select 50 per cent of refraction facilities. The selected facilities were visited for primary data collection. Face‐to‐face interviews were conducted with the managers and the refractionists available in the facilities using a semi‐structured questionnaire. Results Data was collected in 29 centres. All the managers (n=29; response rate 100 per cent) and 50 refractionists (Response rate 65.8 per cent) were interviewed. Optometrists and ophthalmic assistants were the main providers of refraction services (n=70, 92.11 per cent). They were unevenly distributed across the region, highly concentrated around urban areas. The median number of refractions per refractionist per year was 3, 600 (IQR: 2, 400 – 6, 000). Interviewed refractionists stated that clients' knowledge, attitude and practice related factors such as lack of awareness of the need for refraction services and/or availability of existing services were the major barriers to the output of refraction services. The total number of refractions carried out in the Central Region per year was 653, 176. An additional 170 refractionists would be needed to meet the unmet need of 1, 323, 234 refractions. Conclusion The study findings demand a major effort to develop appropriately trained personnel when planning refraction services in the Central Region and in Nepal as a whole. The equitable distribution of the refractionists, their community‐outreach services and awareness raising activities should be emphasised.